Detecting Intestinal Goblet Cells of the Broadgilled Hagfish Eptatretus cirrhatus (Forster, 1801): A Confocal Microscopy Evaluation - Alessio Alesci; Simona Pergolizzi; Serena Savoca; Angelo Fumia; Angelica Mangano; Marco Albano; Emmanuele Messina; Marialuisa Aragona; Patrizia Lo Cascio; Gioele Capillo; Eugenia Rita Lauriano (Biology, 2022)
The fish intestine operates as a complicated interface between the organism and the environment, providing biological and mechanical protections as a result of a viscous layer of mucus released by goblet cells, which serves as a barrier against bacteria, viruses, and other pathogens, and contributes to the functions of the immune system. Therefore, goblet cells have a role in preserving the health of the body by secreting mucus and acting as sentinels. The ancient jawless fish broadgilled hagfish (Eptatretus cirrhatus, Forster, 1801) has a very basic digestive system because it lacks a stomach. By examining the presence, localization, and co-localization of 5-HT, TLR2, iNOS, and Piscidin1, this study intends to provide insight into the potential immune system contributions arranged by the gut goblet cells of broadgilled hagfish. Our results characterize intestinal goblet cells of broadgilled hagfish, for the first time, with the former antibodies, suggesting the hypothesis of conservation of the roles played by these cells also in primitive vertebrates. Moreover, this study deepens the knowledge about the still little-known immune system of hagfish.